(untitled) (Marketing Journal, 2026)
This study examines the international experience of enhancing the economic efficiency of oil and gas companies using the cases of Norway, the United States, Saudi Arabia, and the Russian Federation. The analysis is based on a comparative assessment of the historical stages of sectoral development, the specifics of regulatory and institutional frameworks, technological approaches, and methods of managing resource rent over the period 1990 –2024. The findings identify key determinants of efficiency, including the digital transformation of production and management processes, the standardization of drilling operations, the rational utilization of associated gas, the deepening integration of upstream operations with petrochemical production, the introduction of f lexible fiscal instruments, and the development of service and engineering ecosystems. The study demonstrates that long -term efficiency gains result from a combination of technological modernization, a stable regulatory № 1 -SON YANVA R, 202 6-YIL 61 environment, and strategically structured resource governance. Comparative analysis makes it possible to determine which elements of foreign models can be applied in countries reforming their oil and gas sectors, including Uzbekistan, where the adoption of advanced practices may help reduce costs, increase refining depth, and strengthen the investment attractiveness of the industry.